Comparative Genome Analysis Reveals the Molecular Basis of Niche Adaptation of Staphylococcus epidermidis Strains - Su, Fei; Tian, Rui; Yang, Yi; Li, Hexin; Sun, Gaoyuan; Li, Ying; Han, Bingqing; Xu, Xiaomao; Chen, Xue; Zhao, Gang; Cui, Hongyuan; Xu, Hongtao (Frontiers in Genetics, 2020)
Staphylococcus epidermidis is the most commonly isolated species from human skin and the second leading cause of bloodstream infections. Here, we performed a large-scale comparative study without any pre-assigned reference to identify genomic determinants associated with their diversity and adaptation to various environment. Pan-genome of S. epidermidis is open with 435 core proteins and a pan-genome size of 8034 proteins. Genome-wide phylogenetic tree shows high heterogeneity and suggests that routine whole genome sequencing is a powerful tool to analyze the complex evolutionary process of S. epidermidis and investigate the source of infection. Comparative genome analyses demonstrate a good range of antimicrobial resistance genes, especially those within mobile genetic elements. The complicated relationships of host-bacterium and bacterium-bacterium help S. epidermidis to play a vital role in balancing the epithelial microflora. The highly variable and dynamic nature of the S. epidermidis genome may be the result of its success in adapting to broad habitats, genes related to biofilm formation and cell toxicity are significantly enriched in the blood and skin, demonstrating the potential for identifying risk genotype. This study gives the general landscape of S. epidermidis pan-genome and provides valuable insights into mechanisms for genome evolution and lifestyle adaptation of this ecologically flexible species.